PENGARUH SISTEM INFORMASI KEUANGAN DAN MANAJEMAN SUMBER DAYA MANUSIA TERHADAP PENINGKATAN KINERJA PEGAWAI DI PUSKESMAS SE-KABUPATEN FLORES TIMUR - Pure, Maria Novia; Djou, Laurentius D. Gadi; Banda, Falentina Lucia (Jurnal Riset Ilmu Akuntansi, 2024)
The purpose of this study was to find out that financial information systems and human resource management have an effect on improving employee performance at the Puskesmas. The population of this research is the head of the health center and the treasurer who works within the scope of the health center, East Flores Regency, a total of 63 people. The type of research used in this research is quantitative research. The data used is primary data using a questionnaire. Data were analyzed using multiple linear analysis which was managed through IBM SPSS Statistics ver 25. The test results show that: (1) the tcount value of the Financial Information System variable > ttable (2.640> 1.69236) and a significant level of 0.013 <0.05. These results accept the H1 hypothesis which states that the Financial Information System influences Employee Performance. (2) the tcount value of the Human Resource Management variable > ttable (21.786> 1.69236) and a significant level of 0.000 <0.05. These results accept the H2 hypothesis which states that human resource management influences employee performance.